Grain-Boundary Engineering for Aging and Slow-Crack-Growth Resistant Zirconia. (July 2017) - Zhang, F.; Chevalier, J.; Olagnon, C.; Batuk, M.; Hadermann, J.; Van Meerbeek, B.; Vleugels, J.
Ceramic materials are prone to slow crack growth, resulting in strength degradation over time. Although yttria-stabilized zirconia (Y-TZP) ceramics have higher crack resistance than other dental ceramics, their aging susceptibility threatens their long-term performance in aqueous environments such as the oral cavity. Unfortunately, increasing the aging resistance of Y-TZP ceramics normally reduces their crack resistance. Our recently conducted systematic study of doping 3Y-TZP with various trivalent cations revealed that lanthanum oxide (La2 O3 ) and aluminum oxide (Al2 O3 ) have the most potent effect to retard the aging kinetics of 3Y-TZP. In this study, the crack-propagation behavior of La2 O3 and Al2 O3 co-doped 3Y-TZP ceramics was investigated by double-torsion methods. The grain boundaries were examined using scanning transmission electron microscopy and energy-dispersive spectroscopy (STEM-EDS). Correlating these analytic data with hydrothermal aging studies using different doping systems, a strategy to strongly bind the segregated dopant cations with the oxygen vacancies at the zirconia-grain boundary was found to improve effectively the aging resistance of Y-TZP ceramics without affecting the resistance to crack propagation.